Revenge porn as a form of cyber misogyny - Vilić Vida (Temida)
Among many forms of abuse of privacy in the cyberspace and social media networks, particular attention is given to the so-called cyber misogyny. It refers to the existence of deeply rooted prejudices against women and encompasses various forms of gender- based hatred, harassment and violence against women that occur in a virtual (cyber) space. The subject of this paper is an analysis of emerging forms of cyber misogyny, particularly focusing on one of its most widespread forms: revenge porn. Through revenge porn in the cyberspace, misogyny can be manifested through publishing someone’s intimate photos, that is, photos of their intimate private life or sexually explicit photos and videos. In all these cases, publications in cyberspace or social media occur without the knowledge, willingness or consent of the photographed person. The purpose behind such activity is to shame and/or humiliate the victim by causing her pain and moral suffering for reasons of revenge. The anonymity of the victim is not preserved; on the contrary, her identity and other relevant data are listed in order to identify and make the victim more visible. Therefore, the aim of the paper is to point out to the seriousness of this phenomenon that occurs in the cyberspace, which presents violation of privacy and causes difficult consequences for the victim. Furthermore, the aim is to investigate the possibilities of criminalization and protection of the (mostly female) victims of this criminal act. The main topics analysed in this paper include: a definition of cyber misogyny and revenge porn, an explanation of the most common forms of its manifestation, existing forms of protection, and criminalization of revenge porn worldwide and in the Republic of Serbia.